Accelerated qualification of creep-resistant materials using a datum temperature method (DTM) to calibration. (October 2022) - Cano, Jaime A.; Haque, Mohammad Shafinul; Hossain, Md Abir; Stewart, Calvin M.
Abstract: In this study, the datum temperature method (DTM) is applied to the Wilshire-Cano-Stewart (WCS) model to predict rupture time, minimum-creep-strain-rate, and creep deformation. The datum temperature method (DTM) is an alternative calibration approach that can be applied to existing models to improve accuracy and extrapolation reliability. The availability of creep data is limited due to the time and costs associated with testing. Often data is not available at desired operating conditions or creep life. Although accelerated testing methods have been developed, there is still a need to extrapolate creep data to conditions of interest. Conventional time-temperature-parametric (TTP) models have been used but the need for a decision which TTP model to use for specific materials, the point of convergence, and the inflection points limit their applicability. As an alternative, the DTM is proposed, where all data is transferred to a datum temperature for ease of calibration. In this study, the DTM is combined with the novel continuum damage mechanics based WCS model. To accomplish this, a single heat of alloy P91 from the National Institute of Material Science (NIMS) is considered and the WCS model is calibrated by DTM, and post-audit validated using the remaining heats of materials and an additional creep deformation dataset from Kimura. This calibration approach allows the model to predict rupture, minimum-creep-strain-rate, and creep deformation from a single datum temperature and single heat. It is found that DTM can significantly reduce the time for materials qualification and effort needed for model calibration. Highlights: The datum temperature method (DTM) has two additional equations to predict minimum-creep-strain-rate and creep deformation. The DTM accurately calibrates the WCS model for the prediction of alloy P91 stress-rupture, MCSR, and creep deformation. The datum temperature method is proven to have similar accuracy as conventional calibration methods with a simpler approach.